Managing tensions as paradox in CEO succession: The case of nonfamily CEO in a family firm. (May 2020) - van Helvert-Beugels, Judith; Nordqvist, Mattias; Flören, Roberto
An increasing number of family firms choose to select a nonfamily CEO for the highest executive office. However, appointing a nonfamily CEO in a family firm tends to give rise to tensions that need to be managed for effective work relationships between the nonfamily CEO and the family owners. We draw on insights from the paradox literature to better understand these tensions and how they are managed. We performed real-time, in-depth longitudinal research into one family firm, which appointed a nonfamily CEO, and studied tensions in the work relationships between the nonfamily CEO and the family owners for a period of three years. We identified tensions arising in four specific areas after the transition from a family to a nonfamily CEO: professionalisation, collaboration, resource allocation and role transition. We found new insights regarding how an advisory board can provide support for the family owners in building work relationships with the nonfamily CEO, which makes the tensions salient and possible to manage through a paradox approach. These results inform a perspective of paradox management that shows by whom and how the different tensions are managed, that is, through changes in behaviour and/or through changes in the underlying subsystems of the family firm.